(untitled) (Islamic Sciences Journal, 2023)
We quoted the title of the research from the manuscript, which is a footnote to the explanation of Al-Durr Al-Mukhtar by Al-Hasakfi on the explanation of Matn Tanweer Al-Absar by Al-Tamartachi, for the book “Tuhfat Al-Akhyar Ala Al-Durr Al-Mukhtar” written scattered copies preserved in the libraries of the world, I made sure to collect the best copies that are suitable for investigation. And the one who looks at the heritage books will find scientific valuables left to us by eminent scholars who spent their lives in acquiring knowledge, teaching it and spreading it, and they did their best and worked hard in authoring and classifying until they clarified the problems and solved the dilemmas, so they composed their books according to their discretionary schools. From here emerged the importance of investigating Islamic manuscripts, in order to enable the nation to its heritage, to facilitate access to it, to benefit from it, and to complete what the predecessors of this nation began with. For the manuscript, it is clear that Imam Ibrahim al-Halabi derived most of the jurisprudential issues from the books of jurists and fatwas in the Hanafi school that preceded him or contemporaneously with him. And so on...